2021
DOI: 10.1101/2021.01.16.21249941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxychloroquine and azithromycin: As a double edge sword for COVID-19?

Abstract: BackgroundHydroxychloroquine with or without azithromycin was one of the common therapies at the beginning of the COVID-19 pandemic. They can prolong QT interval, cause Torsade de pointes, and lead to sudden cardiac death. We aimed to assess QT interval prolongation and its risk factors in patients who received hydroxychloroquine with or without azithromycin.MethodsThis was a retrospective cohort study. 172 patients with COVID-19 included, hospitalized at hospitals of Babol University of Medical Sciences betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Quinidine is the most popular subject of the reports on the QT interval prolonging agents and antimalarial drugs 29 . Its chemical structure and function is identical to hydroxychloroquine, which causes an increase of plasma exposure of beta‐blockers that are metabolized to varied rates by CYP2D6 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinidine is the most popular subject of the reports on the QT interval prolonging agents and antimalarial drugs 29 . Its chemical structure and function is identical to hydroxychloroquine, which causes an increase of plasma exposure of beta‐blockers that are metabolized to varied rates by CYP2D6 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Quinidine is the most popular subject of the reports on the QT interval prolonging agents and antimalarial drugs. 29 Its chemical structure and function is identical to hydroxychloroquine, which causes an increase of plasma exposure of beta-blockers that are metabolized to varied rates by CYP2D6. 30 It was reported that hydroxychloroquine effectively inhibited SARS-CoV-2 infection in vitro and have indicated clinical and virologic advantages in COVID-19 patients.…”
Section: F I Gmentioning
confidence: 99%
“…For example, in the Claimed COVID-19 cure case heard in 2021, the Board recommended that Meta publish a transparency report on how the company's Community Standards have been enforced during the COVID-19 pandemic (OSB 2021c). In its initial response to the recommendation, Meta stated that it will "continue to look for ways to communicate the efficacy of our efforts to combat COVID-19 misinformation" (Meta 2021a). Meta's response reframes the recommendation to be about its enforcement on COVID-19-related content, whereas the Board's initial recommendation asked Meta to disclose information about its enforcement generally during the COVID-19 pandemic.…”
Section: Best Practices For Writing Implementable Recommendationsmentioning
confidence: 99%